Analisis Manajemen Sumber Daya Manusia Strategik dalam Upaya Meningkatkan Kinerja Pegawai di Kantor Pengadilan Agama Sumenep - Dewy Arifah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The Sumenep ”Religion Court requires Strategic human resources management  to achieve its goals. Strategic HRM considers the agency strategy implications of the entire human resource system within the agency by translating agency objectives into specific human resource management systems. This study aims to obtain descriptive findings (1) SWOT at the Sumenep Religious Court; (2) Analyzing HRM formulations; (3) Implementation of strategic HRM at the Sumenep Religious Court; (4) Evaluation and control of strategic HRM performance at the Sumenep Religious Court. This research is a descriptive qualitative research. The data collection method uses document recording techniques, interviews, and observations. Data were analyzed using qualitative descriptive analysis and Likert measurement scale. The results of this study indicate that (1) Strengths, weaknesses, opportunities, and threats (SWOT) at the Sumenep Religious Court have been done quite well and correctly by considering the external environment, but there needs to be more serious attention to the internal environment such as there are still employees who are lack of discipline in carrying out the task; (2) The Sumenep Religious Court has formulated Strategic HRM very well, including the vision, mission, goals, objectives and policy direction that will be applied in realizing the Sumenep Religious Court in ACTION (Together, Trustful, Creative, Solutive, Inspirational); (3) Implementation of Strategic HRM performance in the Sumenep Religious Court has been very good because it is in accordance with the program, activities, performance indicators, performance targets that have been set; (4) Evaluation and control of the performance of the Strategic HRM at the Sumenep Religious Court obtained that the performance results are in the good category but there are 3 achievements of the strategic objectives of money not yet achieved."